Dream and the preternatural in the poetry of Walter de la Mare - Townsend, Rosemary (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1984)
From Chapter 1: In this chapter I hope to illustrate in general terms how de la Mare's interest in dream and the preternatural pervades his work. His views on reality and in what it truly consists will be considered and definitions provided of various terms used throughout this study. These will approximate as closely as possible the meanings they acquire through de la Mare's own use of them. Some detailed reference to his work, especially to his prose introduction to the anthology Behold, This Dreamer! and to his poem "Dreams", will provide support for the statements made. Finally, an attempt will be made to place de la Mare, briefly and in broad outline, within his literary context, again with particular reference to his interest in dream and the preternatural and where it corresponds to or deviates from what one could expect from a poet of this period.
Keywords: De la Mare, Walter, 1873-1956 -- Criticism and interpretation